Kształtowanie kompetencji demokratycznych – perspektywa rozwojowa - Błajet, Piotr; Przyborowska, Beata (Wydawnictwo Naukowe UAM, 2014)
Analysis of the situation in Poland and abroad may indicate the illusory nature of the democratic society project. Not infrequently does democracy in many places and processes turn out to be an empty signifier. One of the underlying reasons is the watering down or invalidating differences between individuals. The liberal strategy of leaving out differences seems to be one of the crucial drivers of the crisis of democracy. Meantime, for the democratic project to be operational it must take into account the fact that people differ from one another by means of codes via which they comprehend reality and try to change it. Democracy will be then a strategy of integrating differences. Therefore the project of educating for democracy and developing democratic competences must assume as its starting point some concept of human development. Robert Kegan’s concept of development, contingent on the notion of the object, allows a typology of attitudes towards differences, which in turn allows an adoption of precise education and logistical tasks in the strategy of education for diversity.
Development of Democratic Competences – a Developmental Perspective
Keywords: democratic competencies; integraf development; differences; Kegan’s theory of the